Alcohol purchasing by ill heavy drinkers; cheap alcohol is no single commodity. Issue 12 (December 2015) - Gill, J.; Chick, J.; Black, H.; Rees, C.; O'May, F.; Rush, R.; McPake, B.A.
Abstract: Objectives: Potential strategies to address alcohol misuse remain contentious. We aim to characterise the drink purchases of one population group: heavy drinkers in contact with Scottish health services. We contrast our findings with national sales data and explore the impact of socio-economic status on purchasing behaviour. Study design: Cross-sectional study comparing alcohol purchasing and consumption by heavy drinkers in Edinburgh and Glasgow during 2012. Methods: 639 patients with serious health problems linked to alcohol (recruited within NHS hospital clinics (in- and out-patient settings) 345 in Glasgow, 294 in Edinburgh) responded to a questionnaire documenting demographic data and last week's or a 'typical' weekly consumption (type, brand, volume, price, place of purchase). Scottish Index of Multiple Deprivation quintile was derived as proxy of sociodemographic status. Results: Median consumption was 184.8 (IQR = 162.2) UK units/week paying a mean of 39.7 pence per alcohol unit (£0.397). Off-sales accounted for 95% of purchases with 85% of those <50 pence (£0.5 UK) per alcohol unit. Corresponding figures for the Scottish population are 69% and 60%. The most popular low-priced drinks were white cider, beer and vodka with the most common off-sales outlet being the corner shop, despite supermarkets offering cheaper options. Consumption levels of the cheapest drink (white cider) were similar across all quintiles apart from the least deprived. Conclusions: Heavy drinkers from all quintiles purchase the majority of their drinks from off-sale settings seeking the cheapest drinks, often favouring local suppliers. While beer was popular, recent legislation impacting on the sale of multibuys may prevent the heaviest drinkers benefiting from the lower beer prices available in supermarkets. Non-etheless, drinkers were able to offset higher unit prices with cheaper drink types and maintain high levels of consumption. Whilst price is key, heavy drinkers are influenced by other factors and adapt their purchasing as necessary. Highlights: We surveyed drinking behaviour in 639 patients with alcohol-related harm. Consumption was predominantly from off-sale settings (median = 184.8 UK units/week). Popular drinks were cheap varieties of white cider and vodka. Price and location of point of sale were key drivers of consumption. 85% of units cost less that the proposed minimum unit price for alcohol.